因式分解1、(p^4+q^4)^2-4p^2q^2 2、(3x-2y)^2-16y^2 3、(a+b)^2(b+c-a)

问题描述:

因式分解1、(p^4+q^4)^2-4p^2q^2 2、(3x-2y)^2-16y^2 3、(a+b)^2(b+c-a)(c+a-b)+(a-b)^2(a+b+c)(a+b-c)
1、(p^4+q^4)^2-4p^2q^2
2、(3x-2y)^2-16y^2
3、(a+b)^2(b+c-a)(c+a-b)+(a-b)^2(a+b+c)(a+b-c)
1个回答 分类:数学 2014-11-17

问题解答:

我来补答
1、(p^4+q^4)^2-4p^2q^2
=[(p^4+q^4)+2pq][(p^4+q^4)-2pq]
=(p^4+q^4+2pq)(p^4+q^4-2pq)
(p^4+q^4)^2-4p^4q^4
=[(p^4+q^4)+2p^2q^2][(p^4+q^4)-2p^2q^2]
=(p^2+q^2)^2(p^2-q^2)^2
=(p^2+q^2)^2(p+q)^2(p-q)^2
2、(3x-2y)^2-16y^2
=[(3x-2y)+4y][(3x-2y)-4y]
=(3x+2y)(3x-6y)
3、(a+b)^2(b+c-a)(c+a-b)+(a-b)^2(a+b+c)(a+b-c)
=(a+b)^2[c-(a-b)][c+(a-b)]+(a-b)^2[(a+b)+c][(a+b)-c]
=(a+b)^2[c^2-(a-b)^2]+(a-b)^2[(a+b)^2-c^2]
=(a+b)^2c^2-(a+b)^2(a-b)^2+(a-b)^2(a+b)^2-(a-b)^2c^2
=(a+b)^2c^2-(a-b)^2c^2
=c^2[(a+b)+(a-b)][(a+b)-(a-b)]
=c^2(2a)(2b)
=4abc^2
 
 
展开全文阅读
剩余:2000
下一页:先解十一题